Global warming : a very short introduction - Maslin, Mark (Very short introductions, 2004)
Global Warming is one of the most controversial scientific issues of the twenty first century. This book provides an informative, up-to-date, and readable book about the predicted impacts of global warming and the surprises that could be in store for us in the near future.